2020
DOI: 10.21203/rs.3.rs-50007/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of lncRNA prognostic signature and analysis of their functions for HCV-related hepatocellular carcinoma

Abstract: Background Hepatitis C virus (HCV) infection is a main contribution to the increase in hepatocellular carcinoma (HCC) incidence and patients’ death recently, but prognostic biomarkers for HCV-related HCC remain rarely reported. This study was to identify an lncRNA prognostic signature for HCV-HCC patients and explore their underlying function mechanisms. Methods In total, 102 HCV-HCC samples and 50 normal control samples were obtained from The Cancer Genome Atlas (TCGA) database. Univariate and multivariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Notably, HCC Patients having high LINC01419 and AK021443 expression levels showed significantly lower overall survival as indicated by Kaplan-Meier and Log-rank survival tests. In the same context, it was reported that HCC patients having increased expression levels of AK021443 had shorter OS than those with low AK021443 expression levels, in addition, increased LINC01419 expression was significantly related to a lower OS in HCV-HCC patients [5,31].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Notably, HCC Patients having high LINC01419 and AK021443 expression levels showed significantly lower overall survival as indicated by Kaplan-Meier and Log-rank survival tests. In the same context, it was reported that HCC patients having increased expression levels of AK021443 had shorter OS than those with low AK021443 expression levels, in addition, increased LINC01419 expression was significantly related to a lower OS in HCV-HCC patients [5,31].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, LINC01419 promotes HCC development and metastasis by directing EZH2-regulated RECK [30,31]. Furthermore, the downregulation of LINC01419 inhibits cell migration, invasion, and autophagy via deactivation of the PI3K/Akt1/mTOR pathway [32].…”
Section: Discussionmentioning
confidence: 99%